Effect of sintering temperature on mineral composition and heavy metals mobility in tailings bricks. (15th June 2019) - Wang, Guangwen; Ning, Xun-an; Lu, Xingwen; Lai, Xiaojun; Cai, Haili; Liu, Yuxin; Zhang, Tingsong
Highlights: Cu can be transformed to ferrite spinel with tailings brick raw materials. The phase structure of Zn is affected by the sintering temperature. The leaching rate of Pb is high due to the formation of PbSO4 by sintering. Sintering of the tailings brick raw material effectively fixes heavy metals. Abstract: In this study, the mixing mechanism and phase transition process of different metals during the sintering of tailings bricks with four different metal oxides (CuO, PbO, ZnO, and CdO) at temperatures ranging from 700 to 1100 °C for 2 h were investigated. The properties of the sintered product was characterized and analyzed, and the results showed that the main crystalline phases are quartz, cristobalite, hematite, and mullite while the metal oxides are ascribed to copper ferrite spinel (CuFe2 O4 ), gahnite (ZnAl2 O4 ), zinc ferrite spinel (ZnFe2 O4 ), lead feldspar (PbAl2 Si2 O8 ), and cadmium feldspar (CdAl2 Si2 O8 ). Further analysis indicates that the heavy metals were transited into spinel or silicate structures with favorable efficiency. This indicates a good heavy-metal fixation effect from the structural change after the sintering process. Finally, the leaching experiments of the sintered samples suggest that the metal leaching decreased to a low and stable value when the sintering temperature was higher than 950 °C, which meets the China standard (GB 5085.3-2007). The above results indicate that the sintering process facilitates the combination of Cu, Zn, Pb and Cd offering an effective and safe method for the application of materials that contain tailings.